Ehrlichia canis Vaccine Development: Challenges and Advances - Bruna Samara Alves-Ribeiro; Raiany Borges Duarte; Zara Mariana de Assis-Silva; Ana Paula Carvalho Gomes; Yasodaja Assis Silva; Lizandra Fernandes-Silva; Alice Caroline da Silva Rocha; Iago de Sá Moraes; Klaus Casaro Saturnino; Dirceu Guilherme de Souza Ramos; Isis Indaiara Gonçalves Granjeiro Taques; Ísis Assis Braga (Veterinary Sciences)
Canine monocytic ehrlichiosis (CME) is an infectious disease caused by Ehrlichia canis, a globally recognized obligate intracellular bacterium. In addition to dogs, other animals, including humans, may be affected. Despite its epidemiological importance and impact on public health, there is currently no commercial vaccine against E. canis. This study aimed to present relevant aspects of the challenges and advances encountered in the development of vaccines for CME and highlight perspectives for future investigations. High genetic variability, along with the various evasion mechanisms employed by E. canis, has hindered the identification of an antigen that targets Th1 cells and is immunogenic to most E. canis isolates, considering their genotypic and phenotypic characteristics. The vaccine must predominantly confer cellular and humoral immunity to achieve robust immune responses. Early production efforts have been challenging due to low immunogenicity, difficulties in establishing long-term protection, and limitations of the techniques used. However, with the refinement of bioinformatic tools, research in this area will be facilitated, thereby accelerating the development of effective vaccines for CME. According to these authors, this vaccine should consist of multiple epitopes.